AB0482 Takayasu arteritis and hla-b52 allele: a single-centre analysis from japanese population. (23rd January 2014) - Origuchi, T.; Suzuki, T.; Nakashima, Y.; Horai, Y.; Okada, A.; Kawashiri, S.-Y.; Iwamoto, N.; Ichinose, K.; Arima, K.; Tamai, M.; Nakamura, H.; Eguchi, K.; et al.
Abstract : Background: Takayasu arteritis (TA) is a large vessel vasculitis affecting the aorta and its primary branches. The etiology of TA is still unknown, but recent studies have indicated that some genetic factors involve in its disease process. One of susceptible genes is HLA-B52 allele, however, its role to TA in Japanese populationhas not been well investigated. Objectives: We have tried to investigate whether HLA-B52 allele associate with clinical characteristic of patients with TA from Japanese population. Methods: We have retrospectively collected the patients with TA, diagnosed by the ACR classification criteria, in the medical record of Nagasaki University Hospital from 2003 to 2012. Twenty-five TA patients have been collected. All of patients gave their informed consent to be subjected to the protocol that was approved by the Institutional Review Board of Nagasaki University. Results: Twenty-three out of 25 were female patients. Disease onset was 33.6 ± 18.5 y.o., and 15 patients were younger than 20 y.o. at onset. Initial laboratory data were WBC count 9238 ± 3838/mm 3, CRP 5.8 ± 5.9 mg/dL, IgG 1, 603 ± 520 mg/dL, fibrinogen 506 ± 129 mg/dL, respectively. Antinuclear antibody and rheumatoid factor were positive in two patients. Nineteen patients had been treated with glucocorticoids only whereas immunosuppressive agents were prescribed together with glucocorticoids in 12 patients. HLA typing was examined in 15 out of 25 TA patients. HLA-B52 allele was found in eleven TA patients (73.3%). Although statistical significance was not found, there was a trend that initial CRP (HLA-B52 allele-positive: 6.7 ± 4.1 mg/dL vs HLA-B52 allele-negative: 3.7 ± 3.7 mg/dL) and initial prednisolone dosage (HLA-B52 allele-positive: 37.8 ± 6.70 mg/day vs HLA-B52 allele-negative: 22.5 ± 17.1 mg/day) were high in HLA-B52 allele-positive patients as compared with negative patients. Additionally, five HLA-B52 allele-positive patients received methylprednisolone pulse therapy and eight received immunosuppressive agents whereas none of HLA-B52 allele-negative patients received such regime. Conclusions: Most patients with TA were young female and HLA-B52 allele was frequently found. Presence of HLA-B52 allele might be a prognostic factor in Japanese patients with TA. References: Sahin Z, Bıcakcıgil M, Aksu K, el al. Turkish Takayasu Study Group. Takayasu's arteritis is associated with HLA-B*52, but not with HLA-B*51, in Turkey. Arthritis Res Ther. 2012 Feb 6;14(1):R27. doi: 10.1186/ar3730. Ohigashi H, Haraguchi G, Konishi M, et al. Improved prognosis of Takayasu arteritis over the past decade--comprehensive analysis of 106 patients. Circ J. 2012;76(4):1004-11. Disclosure of Interest: None Declared